(untitled) (International Journal of Economics Management and Social Science, 2026)
In the rapidly evolving landscape of Indonesian higher education, the Master of Management (MM) degree serves as a critical bridge between academic theory and high-level corporate leadership. This article examines the strategic role of Human Resource Management (HRM) in fostering excellence, using a localized lens to explore how institutions—even those in remote regions—balance national accreditation (BAN-PT) with international standards. Specifically, it highlights the case of Universitas Amal Ilmiah (UNAIM) Yapis Wamena, demonstrating how remote institutions can leverage localized HRM and international immersion to produce globally-minded leaders. Drawing on strategic HRM frameworks (Ulrich & Dulebohn, 2015) and internationalization theories (Knight, 2012), this study reveals that institutional transformation in peripheral regions requires adaptive HRM models that integrate cultural competency, digital infrastructure, and cross-border learning experiences. The findings suggest that strategic HRM serves as an equalizer, enabling institutions in remote locations to overcome geographic and resource constraints while producing graduates competitive in the ASEAN Economic Community. Keywords: Strategic HRM, Master of Management, Higher Education Transformation, Internationalization, Remote Institutions, ASEAN Comparative Learning